APC3-A charge sampling, storage and readout chip for silicon detector readout - Borer, K; Munday, D; Parker, M; Anghinolfi, F; Aspell, P; Campbell, M; Jarron, P; Heijne, E; Santiard, J; Verweij, H; Gossling, C; Reichold, A; et al. (1994)
The 'APC3' is a charge sampling and storage chip designed for high speed readout of silicon detectors. It has 32 channels, each with pre-amplifier, integrator and storage capacitors. Current from a silicon detector connected to the input is integrated as a charge and stored on a capacitor. There are 128 capacitors per channel which are used sequentially to store the charge. The charge is held on the storage capacitor until it is either read out or discarded. Logic on the chip manages the storage and retrieval of samples. This logic uses a novel architecture based on a system of pointers and read-out addresses. This paper describes the operation of the chip and measurements of its performance.